An improved lance design for hot metal de-sulphurisation. (3rd July 2017) - Tripathi, P.; Kumar, D. S.; Sah, R.; Sekhar, V. R.
Abstract : Hot metal de-sulphurisation is a dip-lance process involving the pneumatic injection of fine-grained de-sulphurisation reagents into the molten metal. For maximum efficiency the particles must be dispersed in the ladle as widely as possible to increase the total interfacial area which is primarily controlled by the lance design. Seven different lance configurations were modelled and simulated to determine the most efficient design using physical and mathematical modelling approach. A 0.25 scale plexi-glass model of the 100 T hot metal ladle was fabricated for the study. Residence time and mixing time studies were carried out using the electrical conductivity measurement technique through stimulus response of injected saturated salt solution. Mathematical modelling approach using momentum balance was used to simulate fluid flow profile of lance-ladle assembly under operating conditions using computational fluid dynamics package ANSYS-CFX. Based on the studies a new curved port lance has been designed which resulted in uniform and swirling flow profile inside the ladle without rotating the lance. Injection through the new lance increased the residence time of the particles and reduced the dead zones. The new design was fabricated and experimented at de-sulphurisation stations and has resulted in reduced flux consumption and treatment time.